Sequência didática e proposta de nova metodologia de ensino com ênfase no estudo investigativo sobre as parasitoses para alunos de uma escola estadual em Belo Horizonte - Eurípia Leonel Santana (2021)
The traditional form of teaching has been debated for a long time. New methodological approaches that increase the assimilation of content are encouraged. In this context, we articulated and tested a new teaching-learning methodology based on the theory of the law of diffusion and innovation by Everett Rogers, whose theory until the present date had been used for marketing, having as pillars Piagetian constructivism and socio- interactionism adapted to learning Problem-based The study was carried out through the theme of parasites, relevant and close to the reality of the community with 48 students from the 1st year of high school in a state school, on the outskirts of Belo Horizonte. The methodology applied through the discussion of problem situations in small groups, aiming at the interaction and reorganization of knowledge, which were assigned different functions according to their multiple profiles within Rogers' proposal. The results showed a greater integration and appropriation of the parasitic content among students with different profiles. There was active involvement through the generation of investigative questions and problems through the collection, analysis and interpretation of data, leading the students to formulate hypotheses and conclusionsin a reflexive way, emphasizing socio- emotional competences contextualized to the theme. Through a dynamic and replicable methodology, easy to conduct, it can be used for any area of knowledge and age group. The methodology proved to be effective, promoting, in addition to the integration, horizontalization of knowledge and thus the protagonism and empowerment of students, allowing the knowledge established about parasites to contribute to prophylaxis and maintenance of the general health of students.